Conquest and the Law in Swedish Livonia (ca. 1630–1710) : A Case of Legal Pluralism in Early Modern Europe (2017)
In Conquest and the Law in Swedish Livonia (ca. 1630-1710), Heikki Pihlajamäki offers an exciting account of the law in seventeenth-century Livonia, conquered by Sweden. The volume demonstrates how the differences in legal cultures affected the Livonian judiciary and legal procedure in the region. Readership: All interested in the legal history of the early modern period, comparative legal history and the history of the Baltic region.